Anima Mundi the rise of the world soul theory in modern German philosophy - Vassányi, Mikló; SpringerLink (Online service). (Dordrecht [The Netherlands] New York Springer, 2011)
First affirmed by Plato, the concept of the world as a cosmic living being, possessed of a soul, gained great importance in the Stoic and Neo-Platonic philosophical schools. Several medieval philosophers displayed an interest in this theory of the world soul, which retained its attractive power even into the Renaissance. However, the leading early modern rationalists, especially Leibniz, found the world soul philosophically unacceptable. Why and how then did the German Romantics of the late 1700s and early 1800s ? first and foremost Franz von Baader and Schelling ? come resolutely to posit the existence of the world soul? In Anima Mundi: The Rise of the World Soul Theory in Modern German Philosophy , Miklós Vassányi shows that the metaphysical aspirations of the early German Romantics could not be satisfied by the Leibnizian concept of a God beyond the world. Powerful as Leibniz's argument is when primarily the existence of God is considered, it fails to convincingly account for the presence of God within the world, and for the unity of the world. The fundamental existential experience of the Romantics was that God is immediately present in Nature, that God and Nature constitute an indissoluble Absolute. The best philosophical instrument to articulate their theory of the interpenetration of the Finite and the Infinite was a theory of the soul.
Introduction -- Part I: Opposition to the identification of the World Soul with God in the philosophia Leibnitio-Wolffiana : The theory of God as the "ens extramundanum." - Chapter 1: Presentation of the texts relevant for the concept of an "anima mundi." The immediate natural theological setting of the problem -- Chapter 2: The distinctive philosophical content of the concept of an "anima mundi" in Leibniz and his followers. Arguments of this school against the theory of anima mundi. A broader natural philosophical and metaphysical discussion of their answer positions -- Part II: "Les naturalistes" ? XVIIIth-century physico-theology : The scientific demonstration of the existence and attributes of God from the teleology of nature. The World Soul theory in physico-theology. Physico-theology as a source of inspiration for the Romantics -- Chapter 3: Preliminary historical and conceptual presentation of "l?histoire naturelle" in selected major works of some leading naturalists. The relation of natural science to theology or spirituality in their works -- Chapter 4: General philosophical analysis of physico-theology. Part III. Gradual rise of the concept of a World Soul in the ?Lessingszeit?. Philosophical Cabbala, Spinozism and mysticism : Böhme & Ötinger; Spinoza, Lessing, and the Pantheismus-Streit; Giordano Bruno?s influence in the epoch -- Chapter 5. Böhme?s speculative theology (De signatura rerum, 1622). Ötinger?s Cabbalistic theory of the world as a glorious divine epiphany or shekhina & his problematic rejection of the concept of Weltseele (Offentliches Denckmahl der Lehr-tafel einer ? Prinzessin Antonia, 1763) -- Chapter 6: The philosophical incompatibility of Spinoza?s system with the World Soul theory. Bayle?s identification of Spinozism with the World Soul theory, and Wachter?s denial of the same. Lessing?s statement concerning the World Soul, and his alleged Spinozism in Jacobi?s Ueber die Lehre des Spinoza? (1785), Mendelssohn?s Morgenstunden? (1785), and Herder?s Gott. Einige Gespräche (1787). Herder?s rejection of the identification of God with the Weltseele. -- Chapter 7: The World Soul in Giordano Bruno?s De la causa, principio et uno (1584) and De l?infinito, universo e mondi (1584). The revival of Bruno?s philosophy in late XVIIIth-early XIXth century German thought -- Part IV. The philosophical postulation of the World Soul in German Romanticism. Baader and S
Revised: Thesis--Katholieke Universiteit te Leuven, 2
Electronic reproduction.
Keywords: Soul; Ontology; Neoplatonism; Philosophy, German -- 19th century